Disentangling the components of coastal fish biodiversity in southern Brittany by applying an environmental DNA approach. Issue 4 (3rd May 2022) - Rozanski, Romane; Trenkel, Verena M.; Lorance, Pascal; Valentini, Alice; Dejean, Tony; Pellissier, Loïc; Eme, David; Albouy, Camille
Abstract: The global biodiversity crisis from anthropogenic activities significantly weakens the functioning of marine ecosystems and jeopardizes their ecosystem services. Increasing monitoring of marine ecosystems is crucial to understand the breadth of the changes in biodiversity, ecosystem functioning and propose more effective conservation strategies. Such strategies should not only focus on maximizing the number of species (i.e., taxonomic diversity) but also the diversity of phylogenetic histories and ecological functions within communities. To support future conservation decisions, multicomponent biodiversity monitoring can be combined with high‐throughput species assemblage detection methods such as environmental DNA (eDNA) metabarcoding. Here, we used eDNA to assess fish biodiversity along the coast of southern Brittany (France, Iroise Sea). We filtered surface marine water from 17 sampling stations and applied an eDNA metabarcoding approach targeting Actinopterygii and Elasmobranchii taxa. We documented three complementary biodiversity components—taxonomic, phylogenetic, and functional diversity—and three diversity facets—richness, divergence and regularity. We identified a north/south contrast with higher diversity for the three facets of the biodiversity components in the northern part of the study area. The northern communities showed higher species richness, stronger phylogenetic overdispersion and lower functional clustering compared to the ones in the southern part, due to the higher diversity of habitats (reefs, rocky shores) and restricted access for fishing. Moreover, we also detected a higher level of taxonomic, phylogenetic, and functional uniqueness in many offshore stations compared to more coastal ones, with the presence of species typically living at greater depths (> 300 m), which suggests an influence of hydrodynamic structures and currents on eDNA dispersion and hence sample composition. eDNA metabarcoding can, therefore, be used as an efficient sampling method to reveal fine‐scale community compositions and in combination with functional and phylogenetic information to document multicomponent biodiversity gradients in coastal marine systems. Abstract : By filtering surface marine water and using eDNA we assessed fish biodiversity along the coast of southern Brittany (Iroise Sea). For Actinopterygii and Elasmobranchii taxa, we documented three complementary biodiversity components ‐ taxonomic, phylogenetic and functional diversity ‐ and three diversity facets ‐ richness, divergence and regularity. We identified a north/south gradient with a higher diversity for the three facets of the biodiversity components in the northern part of the study area.